Resiliencia comunitaria en personas víctimas de violencia política vinculadas a organizaciones sociales y comunitarias en Colombia 2019 (2019)
Colombia is a country with several events of political violence since a long time, this situation turns the country in the second one in the world with forcing migration; because of this the social networks in populations have been broken. Our research is situated in a reading of adversity and social recovery and shows the resiliency as an alternative approach on traditional psychology and social sciences, it states the need to search and to intervene the impact of political violence and its types of recovery. This research focus on resiliency as psychosocial category and possibility of social development. On a phenomenological approach and using the life story and deep interview we look for experiences of resiliency in life path of victims, also we characterize social and resistance practices made by these persons. From them we explored the dynamics of transformation of subjectivity, particularly the sociopolitical and affective dimensions. By this way, we describe psychosocial process around recovery and dynamics that underlie processes of political and affective subjectivation